Accessing stable zirconium carboxy-aminophosphonate nanosheets as support for highly active Pd nanoparticles. Issue 88 (18th September 2015) - Costantino, Ferdinando; Vivani, Riccardo; Bastianini, Maria; Ortolani, Luca; Piermatti, Oriana; Nocchetti, Morena; Vaccaro, Luigi
Abstract : PdNPs stabilized on exfoliated layered zirconium phosphate–carboxyphosphonate nanosheets as an efficient catalytic system for the Suzuki coupling. Abstract : Thin nanosheets from a layered zirconium phosphate–carboxyphosphonate is reported here. Small Pd nanoparticles have been supported on these nanosheets by an efficient method. The resulting Pd-catalyst was fully characterized and tested in the Suzuki–Miyaura coupling. The catalytic system proved its efficiency as it was reused for several cycles and showed low Pd leaching.